2012
DOI: 10.1177/1753193412469781
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outcomes of carpal tunnel release in diabetic and non-diabetic patients

Abstract: The coexistence of diabetes might complicate the diagnosis and operative outcomes of carpal tunnel syndrome. We retrospectively compared the results of carpal tunnel release in diabetic and non-diabetic patients. The group included 386 patients, 322 female (83%) and 64 male (17%) with a mean age of 57 years. A total of 41 patients (11%) were diabetic, whereas 345 (89%) did not have diabetes. Patients were followed-up at six months, by assessments that included Levine scores, filament tests, grip and pinch stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 8 publications
3
39
0
Order By: Relevance
“…Prior studies have produced conflicting results. 11,18,19 The most recent high-quality study 20 found no difference in outcome between 35 diabetic and 31 nondiabetic patients 5 years after carpal tunnel surgery. Our data include a considerably larger sample of diabetic patients with a wide range of types and durations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have produced conflicting results. 11,18,19 The most recent high-quality study 20 found no difference in outcome between 35 diabetic and 31 nondiabetic patients 5 years after carpal tunnel surgery. Our data include a considerably larger sample of diabetic patients with a wide range of types and durations.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between diabetes and surgical outcome CARPAL TUNNEL SYNDROME AND METABOLIC SYNDROME after CTR has been controversial. Some studies have reported beneficial outcome after CTR 21,22 whereas others have demonstrated a negative impact of diabetes on surgical outcome. 23e25 In this study, metabolic syndrome was related to a more severe grade of CTS and was a risk factor for delayed functional recovery at up to 6 months' follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…The patients were followed up at 6 months, by the Levine scores, filament tests, and grip and pinch strength. No significant differences in any of the measured variables were found, which suggests that CTR in diabetic and non-diabetic patients is similarly beneficial [29]. Likewise, Mondelli et al (2004) reported that diabetes had no effect on the final results of the treatment [30].…”
Section: A Diabetesmentioning
confidence: 96%
“…15 articles were reviewed to analyse possible effect of this variable on outcomes[20,23,[28][29][30][31][32][33][34][35][36][37][38][39][40].…”
mentioning
confidence: 99%